2021
DOI: 10.3390/ma14092378
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Ultrahigh-Performance Concrete Tunnel Lining Segments

Abstract: Ultrahigh-performance concrete (UHPC) is a novel material demonstrating superior mechanical, durability and sustainability performance. However, its implementation in massive structures is hampered by its high initial cost and the lack of stakeholders’ confidence, especially in developing countries. Therefore, the present study explores, for the first time, a novel application of UHPC, incorporating hybrid steel fibers in precast tunnel lining segments. Reduced scale curved tunnel lining segments were cast usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Not only are the values of the flexural strength reflected in the studies on FRC, but the failure modes for specimens in flexural tests show similarities with other research. Abbas et al [66] tested tunnel lining segments using UHPC with fiber dosage where the crack developed during the progression of load in the middle part of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are the values of the flexural strength reflected in the studies on FRC, but the failure modes for specimens in flexural tests show similarities with other research. Abbas et al [66] tested tunnel lining segments using UHPC with fiber dosage where the crack developed during the progression of load in the middle part of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Adding fibers improve the mechanical structure behavior and reduce the overall construction cost by reducing the rebars number. 5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The durability and structural performance of tunnel lining segments were investigated by Abbas et al 13 This study was performed on full-scale samples that compared the performance of the steel fiber reinforced concrete (SFRC) segment with the conventional reinforced concrete (RC) segment. Finally, it was concluded that due to the presence of fibers in the concrete volume, the postcracking behavior of SFRC samples has been significantly better and has improved compared to conventional samples.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Abbas and Nehdi conducted thrust load test to study the behavior of precast UHPC segments. 19 They observed that the segments without fibers incurred excessive cracks and concrete spalling under the thrust loads. However, a better performance was observed for segments with steel fibers, indicating their capability to resist typical thrust loads.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent decades have witnessed the emergence of ultra-high-performance concrete (UHPC) as a promising cementitious material in buildings [1], bridges [2], and tunnels [3], etc., due to its excellent tensile and compressive strength [4], agreed post-cracking behaviors [5], and enhanced durability [6]. Extensive application of UHPC materials to fully replace normal-strength concrete (NC) would render the cost prohibitively high [7].…”
Section: Introductionmentioning
confidence: 99%